Economic and environmental evaluation of municipal waste – new fermentation technology of small-scale biogas stations - Kubáňková, Marie; Hyršlová, Jaroslava; Nedělník, Jan; Rusín, Jiří; Chamrádová, Kateřina (Melandrium, 2017)
Solid waste has significant impacts on the environment. As a result of changes in consumers’ habits in recent years, the volume of solid waste is constantly growing. Public administrations attempt to treat solid waste in an environmentally friendly way. There are many efforts being made for the integrated management of solid waste, a comprehensive solution to its disposal and recovery with elimination of the environmental consequences and social impacts, both at EU and regional levels. The EU announced targets for reducing the amount of landfilled biodegradable waste, which prevents the storage of organic matter in landfills from 2016. In accordance with this Directive, it is necessary that partly composted or processed form of digestion exists. The aim of this paper is to present approaches to economic and environmental assessment of selected technologies for the processing of municipal waste, with close attention being paid to a new technology, and the fermentation process of small-scale biogas stations.
Ekonomické a environmentální hodnocení komunálních odpadů - nová technologie fermentace v malých bioplynových stanicích
Keywords: environmental evaluation; economic appraisal; municipal waste; anaerobic digestion; environmentální hodnocení; ekonomické hodnocení; komunální odpad; anaerobní digesce